1998
DOI: 10.1094/pdis.1998.82.5.537
|View full text |Cite
|
Sign up to set email alerts
|

Biological Species of Armillaria in Japan

Abstract: Pairing tests with isolates of Armillaria in culture were used to identify species of Armillaria and their distribution throughout Japan. The existence of 10 intersterile groups of Armillaria was determined by pairing haploid single spore isolates obtained from 20 basidiocarps from a wide geographic distribution in Japan. Two to four haploid tester isolates from each intersterile group were then paired to biological and morphological species with haploid tester isolates from Europe and North America identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 15 publications
3
53
0
Order By: Relevance
“…A. novaezelandiae was found on the native trees Nothofagus dombeyi and N. alpina and on the exotics Pseudotsuga menziesii and P radiata. These results are consistent with the view of Gregory et al (1991) and Ota et al (1998) that differences in host range and geographical distributions sometimes become more apparent after morphological studies of Armillaria specimens have been completed.…”
supporting
confidence: 92%
“…A. novaezelandiae was found on the native trees Nothofagus dombeyi and N. alpina and on the exotics Pseudotsuga menziesii and P radiata. These results are consistent with the view of Gregory et al (1991) and Ota et al (1998) that differences in host range and geographical distributions sometimes become more apparent after morphological studies of Armillaria specimens have been completed.…”
supporting
confidence: 92%
“…nabsnona is reported as a species distributed on the west coast of North America and its range was described primarily in hardwoods of riparian areas. 30) Ota et al 31) have described the occurrence of A. nabsnona in the region of Honshu island, in central Japan. Based on mating tests, Mohammed et al 32) reported a compatible pairing of an isolate collected from Hokkaido Prefecture (Japan) with an Armillaria species described as NABS IX.…”
Section: Discussionmentioning
confidence: 99%
“…nipponica, A. sinapina, A. gallica, A. ostoyae, A. cepistipes, A. ectypa, A. jezoensis, A. singula, A. nabsnona and various unnamed biological species from South East Asia (Sung et al 1989(Sung et al , 1992Mohammed et al 1994;Cha and Igarashi 1995;Sung et al 1995;Ota et al 1998Ota et al , 2009). …”
Section: Introductionmentioning
confidence: 99%